Pengaruh Kualitas Pelayanan dan Religiusitas Terhadap Minat Menabung di Bank Syariah Indonesia - Alwahidin; Nur Afni (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to examine the effect of service quality and religiosity on the intention to save at Bank Syariah Indonesia. This study uses quantitative research methods to confirm the data obtained in the field with the existing theory. Meanwhile, sample data collection techniques were carried out using the questionnaire method, literature study, and documentation. Data is processed using the SmartPLS 3.0 program. The data processing results show that service quality and religiosity have a significant effect on the interest in saving at Bank Syariah Indonesia. This finding is evidenced by each Path Coefficient value > 0.05. First, the service quality variable with the path coefficient value in the hypothesis test is t statistic > t table (2.467 > 1.985) or p-value 0.014 <0.05, so it can be concluded that the service quality variable influences the intention to save at BSI. Second, the Religiosity variable with the path coefficient value in the hypothesis test is t statistic > t table (6.306 > 1.985). So it can be concluded that the religiosity variable influences the intention to save at Bank Syariah Indonesia. The implications of this relevant research are for banks to pay attention again to the influences on customers' interest in keeping at Bank Syariah Indonesia.